Recycling potential of air pollution control residue from sewage sludge thermal treatment as artificial lightweight aggregates - Bialowiec, Andrzej (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2014)
Thermal treatment of sewage sludge produces fly ash, also known as the air pollution control residue (APCR), which may be recycled as a component of artificial lightweight aggregates (ALWA). Properties of APCR are typical: high content of Ca, Mg, P2O5, as well as potential to induce alkaline reactions. These properties indicate that ALWA prepared with a high content of APCR may remove heavy metals, phosphorus, and ammonium nitrogen from wastewater with high efficiency. The aim of this preliminary study was to determine the optimal composition of ALWA for potential use as a filter media in wastewater treatment systems. Five kinds of ALWA were produced, with different proportions of ash (shown as percentages in subscripts) in mixture with bentonite: ALWA0 (reference), ALWA12.5, ALWA25, ALWA50, and ALWA100. The following parameters of ALWA were determined: density, bulk density, compressive strength, hydraulic conductivity, and removal efficiency of ions Zn(2+), NH4 (+), and PO4 (3-). Tests showed that ALWA had good mechanical and hydraulic properties, and might be used in wastewater filtering systems. Phosphates and zinc ions were removed with high efficiency (80-96%) by ALWA25-100 in static (batch) conditions. The efficiency of ammonium nitrogen removal was low, <18%. Artificial wastewater treatment performance in dynamic conditions (through-flow), showed increasing removal efficiency of Zn(2+), PO4 (3-) with a decrease in flow rate